2022
DOI: 10.1007/s00268-022-06737-0
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal Cholecystectomy Results in High Peri‐operative Morbidity and Its Risk‐Profile Should be Emphasised During Consent

Abstract: Background Subtotal cholecystectomy aims to reduce the likelihood of bile duct injury but risks a multitude of less severe, yet significant complications. The primary aim of the present study was to report peri-operative outcomes of subtotal laparoscopic cholecystectomy (SLC) relative to total laparoscopic cholecystectomy (TLC) to inform the consent process. Method All laparoscopic cholecystectomies between 2015 and 2020 in one health board were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…It should be noted that not only was this study conducted outside of the US, but the authors also do not indicate a timeframe for readmission. 18 It should be noted that both of these studies use propensity matching, which may have introduced bias by further reducing sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that not only was this study conducted outside of the US, but the authors also do not indicate a timeframe for readmission. 18 It should be noted that both of these studies use propensity matching, which may have introduced bias by further reducing sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of evidence was assessed by using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) Working Group Criteria. 20 The quality of evidence was high to moderate in five studies 13,15,16,18,19 and low in two studies 14,17 (Supplementary file: eTable 2). The risk of bias was evaluated using the Joanna Briggs Institute (JBI) critical appraisal checklist for observational studies (Supplementary file: eTable 3).…”
Section: Methodsmentioning
confidence: 99%
“…Three studies evaluated the rate of subhepatic collection. 12,13,15 Two studies 12,13 found a greater rate of subhepatic collection in the subtotal cohort, and one study 15 found no difference. Seven studies evaluated inhospital mortality, of which one study 19 reported significantly higher in-hospital mortality in the subtotal group compared to the total group, and six studies [13][14][15][16][17][18] did not find a significant difference between cohorts.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations